Ancient DNA Analysis and Stable Isotope Ecology of Sea Turtles (Cheloniidae) from the Gold Rush-era (1850s) Eastern Pacific Ocean. (30th May 2018) - Conrad, Cyler; Barceló, Laura Pagès; Seminoff, Jeffrey A.; Tomaszewicz, Calandra Turner; Labonte, Marie; Kemp, Brian M.; Jones, Emily Lena; Stoyka, Michael; Bruner, Kale; Pastron, Allen
Historical and archaeological evidence documents the importation of sea turtles from the eastern Pacific Ocean (Baja California) to California during the Gold Rush (1848–1855) and through the end of 19 th century, but it is unknown whether these 19 th century sea turtles foraged in similar ways to their modern counterparts. To identify the species of two Gold Rush-era sea turtle specimens recovered from archaeological deposits in San Francisco, California, we first analyze ancient DNA (aDNA). We then analyze carbon (δ 13 Ccol ), nitrogen (δ 15 N), and hydrogen (δD) stable isotopes of bone collagen and carbon (δ 13 Cap ) and oxygen (δ 18 Oap ) stable isotopes of bone apatite to test if eastern Pacific sea turtle diets have changed over the past 160 years. Ancient DNA confirms that both archaeological specimens are green sea turtles ( Chelonia mydas ). The stable isotope values from the 19 th -century specimens are statistically indistinguishable from the modern comparatives in both δ 13 Ccol and δ 15 N, suggesting that green sea turtle dietary intake has remained relatively unchanged since the 1850s. However, the values are unclear for δD and δ 18 Oap and require additional research. Social Media: Ancient DNA and isotopic analysis of 1850s sea turtles suggest stability in sea turtle foraging through time despite environmental changes.